BOARD CHARACTERISTICS AND ENVIRONMENTAL PERFORMANCE : DOES OWNERSHIP MODERATE THE IMPACT? - Hesniati, Hesniati; Sonata, Vina; Haryanto, Hery (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2024)
The aim of this research is to examine the influence of ownership in moderating corporate governance on environmental performance. The analysis method employed is panel data regression and Moderated Regression Analysis on 52 companies in the energy sector listed on the Indonesia Stock Exchange during 2018-2022. Managerial ownership can strengthen the influence of board size and environmental committee on environmental performance positively and weaken board independence on environmental performance. Meanwhile, blockholder ownership reinforces the influence of board size on environmental performance. Managers play a role in enhancing the participation of boards and environmental committees in environmental practices. Blockholders from other fields need to improve their mastery of environmental practices. Originality of this research is diverse findings highlight the roles of managerial ownership and blockholder ownership in environmental performance, as well as the moderating role of ownership type in corporate governance on environmental performance. The findings of this research provide a new gap for academics to further examine the characteristics of blockholders.